A fighting chance [compact disc, unabridged] - Warren, Elizabeth (Macmillan Audio, 2014)
An unlikely political star tells the inspiring story of the two-decade journey that taught her how Washington really works; and really doesn't. In this passionate, funny, rabble-rousing book, Elizabeth Warren shows why she has chosen to fight tooth and nail for the middle class, and why she has become a hero to all those who believe that America's government can and must do better for working families.